Prolonged Persistence of Chimeric Antigen Receptor (CAR) T Cell in Adoptive Cancer Immunotherapy: Challenges and Ways Forward - Jafarzadeh, Leila; Masoumi, Elham; Fallah-Mehrjardi, Keyvan; Mirzaei, Hamid Reza; Hadjati, Jamshid (Frontiers in Immunology, 2020)
CAR T cell qualities, such as persistence and functionality play important roles in determining the outcome of cancer immunotherapy. In spite of full functionality, it has been shown that poor persistence of CAR T cells can limit an effective antitumor immune response. Here, we outline specific strategies that can be employed to overcome intrinsic and extrinsic barriers to CAR T cell persistence. We also offer our viewpoint on how growing use of CAR T cells in various cancers may require modifications in the intrinsic and extrinsic survival signals of CAR T cells. We anticipate these amendments will additionally provide the rationales for generation of more persistent, and thereby, more effective CAR T cell treatments.